Transcriptome and Metabolome Profiling of a Novel Isolate Chlorella sorokiniana G32 (Chlorophyta) Displaying Enhanced Starch Accumulation at High Growth Rate Under Mixotrophic Condition - Zhu, Qingling; Zhang, Mengmeng; Liu, Bingying; Wen, Fang; Yang, Zhili; Liu, Jianhua (Frontiers in Microbiology, 2022)
Chlorella sorokiniana is one of the most productive microalgal species with high potential for production of biofuels and high value-added molecules. Many studies have focused on its capability of mixotrophic growth using reduced organic carbon and growth pattern shift between autotrophic and mixotrophic conditions. In this study, we investigated growth patterns of a novel isolate C. sorokiniana G32 under mixotrophic growth conditions supplemented with low level (0.125% w/v) and high level (0.5% w/v) of glucose using physiologic, RNA-seq-based transcriptomic, and LC-MS/MS-based metabolomic methodologies. We showed that, maximum OD680 measurement of G32 culture with high glucose supplement in shaking flask was ~ 4-fold higher than that of low glucose supplement. Photosynthetic efficiency (Fv/Fm) in G32 mixotrophic cultures with high or low glucose supplements remains identical to that of G32 phototrophic growth. Notably, we found that the conversion rate between OD680 value and CDW in culture with high glucose supplement was lower than that with low glucose supplement, suggesting that cell-mass density in culture with high glucose supplement was higher than that with low glucose supplement. This high cell-mass density was further confirmed by analysis using sucrose density gradient centrifugation, which was most likely attributed to the high-level accumulation of starch. RNA-seq-based transcriptomic analysis of G32 cultures in response to reciprocal change of glucose supplement levels identified a subset of common DEGs, whose transcription level change correlated with glucose supplement level change, designated as glucose-specific responsive genes. Common DEGs enriched for a number of energy metabolic pathways. Combining with the LC-MS/MS-based metabolomic analysis, we show that high-level supplemented glucose was preferentially oxidized through oxidative pentose phosphate pathway. Taken together, our results provide insight into mechanisms for glucose assimilation under mixotrophic growth in C. sorokiniana G32. Given the fact that increased accumulation of starch without impeding growth rate under mixotrophic growth, we propose that C. sorokiniana G32 have potential for production of high value-added molecules.